BoLA-DRB3 gene haplotypes show divergence in native Sudanese cattle from taurine and indicine breeds - Salim, Bashir (2021)
Autochthonous Sudanese cattle breeds, namely Baggara for beef and Butana and Kenana for dairy, are characterized by their adaptive characteristics and high performance in hot and dry agro-ecosystems. They are thus used largely by nomadic and semi-nomadic pastoralists. We analyzed the diversity and genetic structure of the BoLA-DRB3 gene, a genetic locus linked to the immune response, for the indigenous cattle of Sudan and in the context of the global cattle repository. Blood samples (n=225) were taken from three indigenous breeds (Baggara; n=113, Butana; n= 60 and Kenana; n=52) distributed across six regions of Sudan. Nucleotide sequences were genotyped using the sequence-based typing method. We describe 53 alleles, including seven novel alleles. Principal component analysis (PCA) of the protein pockets implicated in the antigen-binding function of the MHC complex revealed that pockets 4 and 9 (respectively) differentiate Kenana-Baggara and Kenana-Butana breeds from other breeds. Venn analysis of Sudanese, Southeast Asian, European and American cattle breeds with 115 alleles showed 14 were unique to Sudanese breeds. Gene frequency distributions of Baggara cattle showed an even distribution suggesting balancing selection, while the selection index (ω) revealed the presence of diversifying selection in several amino acid sites along the BoLA-DRB3 exon 2 of these native breeds. The results of several PCA were in agreement with clustering patterns observed on the neighbor joining (NJ) trees. These results provide insight into their high survival rate for different tropical diseases and their reproductive capacity in Sudan´s harsh environment.